Sanitary surveillance of wild peneidae in the main tidal channels of Tumbes, Peru - Pretell-Monzón, Krizia (2020)
The tidal channels in the department of Tumbes, Peru harbor various species of penaeids, such as Penaeus stylirostris and P. vannamei, the latter of great economic importance for the country. In 2017, 560 specimens of wild prawns were evaluated in two sampling periods (May-June and September-November), from seven tidal channels to determine the prevalence of notifiable diseases: White Spot Syndrome (WSSV), Infectious Hypodermal and Hematopoietic Infection (IHHNV), Hepatopancreatic Necrosis (NHP), Taura Syndrome (TSV), Infectious Myonecrosis (IMNV) and Yellow Head Syndrome (YHV) using the PCR technique. The presence of three of the seven pathogens was detected. The highest prevalence of the study was VNHHI (6.35%) distributed in the seven tidal channels, followed by HPN (2.65%) in five tidal channels and VSMB (0.55%) present in three channels, but only in the first sampling period.